Digital Strategies in Social Marketing to Promote Puuc Food Culture in Yucatan. - Vargas Jiménez, Monserrat; Domínguez Castillo, José Gabriel (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To develop a social marketing proposal with effectively designed social action efforts aimed at influencing behavioral changes and impacting the inhabitants of the Puuc Biocultural region in Yucatan, Mexico.MATERIAL AND METHOD: The research is descriptive, non-experimental and quantitative and involved the administration of two instruments applied to inhabitants of the region; the first one to learn about eating habits and the second one about the most used means of communication.RESULTS: Among the main findings, evidence was found on the consumption of processed and ultra-processed foods that brings as an effect the loss of food culture. Also, access to the internet and the use of social networks have managed to penetrate in a vertiginous way, being WhatsApp and Facebook those with a higher frequency of use among the inhabitants of these contexts.CONCLUSIONS: This work provided insight into the habits of the target audience and facilitated the design of messages and strategies for digital media, as distribution channels adapted to the context. The results are discussed in the light of scientific studies focused on food culture in Mexico; and the availability and use of information and communication technologies.
Keywords: Food; Culture; Social marketing; Social networks.